2007
DOI: 10.1109/jqe.2007.904306
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Frequency Chirp in Quantum-Dot Semiconductor Lasers

Abstract: We present a numerical model for the analysis of the chirp dynamics of quantum-dot (QD) semiconductor laser under large signal current modulation. The model is based on the multipopulation rate equation formalism, and it includes all the peculiar characteristics of the active QD material such as the inhomogeneous broadening of the gain spectrum, the presence of an excited state confined in the QDs and the presence of nonconfined states due to the wetting layer and the barrier. In this paper the model is applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 22 publications
2
54
0
2
Order By: Relevance
“…Furthermore, a strong dependence on the pump current has been observed [SU05a,JIA12]. Theoretical works have shown that the α-factor measurements in quantum-dot lasers will yield different results depending on the measurement procedure and operating parameters [MEL06,GIO07,LIN12a].…”
Section: Amplitude-phase Coupling In Quantum-dot Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a strong dependence on the pump current has been observed [SU05a,JIA12]. Theoretical works have shown that the α-factor measurements in quantum-dot lasers will yield different results depending on the measurement procedure and operating parameters [MEL06,GIO07,LIN12a].…”
Section: Amplitude-phase Coupling In Quantum-dot Lasersmentioning
confidence: 99%
“…Even then, however, the averaged values calculate to α J ≈ 2.1 for the pump-current perturbation and α E ≈ 0.73 with the injected optical pulse. Thus, even around the same fixed point, no uniform value of an average α can be defined [GIO07,LIN12b]. The α- factor is therefore an inappropriate measure for describing the gain dynamics of the quantum-dot medium.…”
Section: Quantum-dot Laser Dynamicsmentioning
confidence: 99%
“…In the above equations tph is the photon lifetime in the laser cavity, c is the free-space light velocity, nr is the active material refractive index, k is the intensity of feedback light, w0 is the angular frequency of the solitary laser, td is the external cavity roundtrip time and δf is the frequency chirp calculated according to (Gioannini, 2007). Finally, the terms inside the summation operator is the material gain coupling cavity photons and carriers of the ground-, first-and second-excited states.…”
Section: Rate-equationsmentioning
confidence: 99%
“…C g = πe 2h /cn r ε 0 m 2 0 is a constant; N W is the number of QD layers; H act is the average active quantum dot layer thickness; |P σ G S,E S | 2 Capture time from WL to ES τ c0 = 1 ps (Bogaart et al 2005) Capture time from ES to GS τ d0 = 1 ps (Bogaart et al 2005) Carrier escape time from WL to SCH τ qe =3 ns (Gioannini and Montrosset 2007) Carrier recombination time in SCH τ sr = 4.5 ns (Gioannini and Montrosset 2007) Carrier recombination time in WL 2 ps < τ qr < 100 ps Fit…”
Section: Quantum Dot Amplifier Gain Modelmentioning
confidence: 99%
“…The modeling of QD materials is more involved than the modeling of bulk or quantum well gain material due to the inhomogeneous character of the QD gain material. Extensive QD models have been presented especially for In x Ga 1−x As/GaAs QD materials (Sugawara et al 2000;Gioannini and Montrosset 2007) but also for InAs/InP QD materials (Grillot et al 2009) Here we have simplified a commonly used QD amplifier model to calculate the small signal gain spectrum of the amplifiers and to fit a number of the model parameters to the experimental data. Three important parameters are the electron-hole transition energies of the wetting layer (WL), the excited state (ES) and the ground state (GS).…”
Section: Introductionmentioning
confidence: 99%